(untitled) (Journal of the College of Basic Education, 2022)
The wines are one of the poetic purposes that took place in reality and in artEspecially in the Abbasid era, which is an era of mixing, mixing and homogeneity of a variety of culturesTraditions, ideas and beliefs hint at the spirit of renewal and its strength and the features of exclusivity and rebellion against everythingIt is ancient, whose effects are clear, and we seek its changes through the elements of creativity and creativity that are revealedAbout it the poet’s ability on the one hand, and formation, change and composition on the other hand »as well asRedrawing what is familiar and circulating with a distinctive spiritual vision that brings language and poetic image out ofThe circle of repetition writes eternity to its poet in the space of poetic creativity.